2000
DOI: 10.1055/s-2000-10659
|View full text |Cite
|
Sign up to set email alerts
|

Instabile kindliche Femur- und Unterarmschaftfrakturen - Vergleich zwischen konservativer Behandlung und stabiler intramedullärer Schienung -

Abstract: Elastic intramedullary nailing represents a new surgical concept in the treatment of unstable shaft fractures in children. The present case control study wanted to examine the superiority of intramedullary nailing in comparison to conservative therapeutic concepts which had been applied so far. 13 children with forearm fractures who were treated initially by conservative measures were compared to 13 other children who received a primary intramedullary nailing. With femoral fractures, 12 children were included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 8 publications
1
1
0
2
Order By: Relevance
“…Secondary displacement, which is a particular problem for conservative management of these injuries, and leads to malunion or need for re-reduction, is very seldom observed in patients treated with TENS. A comparative study showed that fewer radiologic investigations were necessary after TENS than after conservative therapy (26) , in our study no such complication observed. Another typical complication of forearm fractures treated conservatively is refracture, which has been quoted to occur in (6 10%) of patients (9) .…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…Secondary displacement, which is a particular problem for conservative management of these injuries, and leads to malunion or need for re-reduction, is very seldom observed in patients treated with TENS. A comparative study showed that fewer radiologic investigations were necessary after TENS than after conservative therapy (26) , in our study no such complication observed. Another typical complication of forearm fractures treated conservatively is refracture, which has been quoted to occur in (6 10%) of patients (9) .…”
Section: Discussionsupporting
confidence: 42%
“…More studies (24,25) have shown that even 101 of angulation can lead to decreased rotational mobility. Hertlein (26) showed in a prospective, comparative study that the presence of angulation greater than 10° was significantly rarer (P<0.05) in patients treated with TENS than in patients treated conservatively. In a study from Lee et al (27) , all forearm fractures healed after TENS with angulation less than 5°.…”
Section: Discussionmentioning
confidence: 99%
“…Von mehreren Untersuchern [5,30] konnte gezeigt werden, dass schon Achsenfehler von 10 Grad die Unterarmumwendbewegungen einschränken können. Hertlein [9] konnte in einer prospektiv vergleichenden Untersuchung zeigen, dass nach der ESIN signifikant (p < 0,05) weniger Achsenfehler > 10 Grad auftreten als bei der konservativen Behandlung. In einer Untersuchung von Lee u. Mitarb.…”
Section: Diskussionunclassified
“…In einer vergleichenden Untersuchung konnte gezeigt werden, dass nach der ESIN insgesamt weniger Röntgenkontrollen erforderlich sind als bei der konservativen Behandlung[9].Das für die konservative Behandlung typische Problem einer Refraktur, deren Häufigkeit mit 6 ± 10%[13] angegeben wird, ist nach der ESIN mit etwa 0,5 %[27] eine Rarität. In einer aktuellen Untersuchung[20] wird beschrieben, dass die Reposition einer Refraktur, die einen Monat nach der Osteosynthese auftrat, bei liegenden Implantaten durchgeführt wurde und die Fraktur danach ausheilte.Shoemaker[31] berichtete in seinem Krankengut von 32 Patienten über 3 sekundäre Repositionsverluste sowie 2 Refrakturen, die nach der Metallentfernung auftraten.…”
unclassified